The Space Conductors Are Among Us. - Vijlbrief, Nienke; van de Werdt, Rob; Happel, Peter; Marchesini, Valeria (Amsterdam : P/////AKT, 2021)
Ådlandsvik, Stian ; Serapinas, Augustas ; Blumenschein, Stephan ; Kraule-Kűna & Vítola, Elina ; Vahtra, Anu
The Space Conductors Are Among Us, P/////AKT, Amsterdam, januari 2020 - april 2021
boek